RELATIONSHIP BETWEEN THE HEALTHY INDONESIA PROGRAM FAMILY APPROACH (PIS-PK): INDICATORS OF NUTRITION, MATERNAL AND CHILD HEALTH WITH STUNTING IN THE FIRST 1000 DAYS OF LIFE IN THE LUT TAWAR COMMUNITY HEALTH CENTER WORKING AREA - Anggi, Tri Yayang; Arlianti, Nopa; Amin, Fauzi Ali (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2023)
Background: Indonesia is still experiencing problems in child nutrition and growth and development, one of which is stunting. Aceh is one of the provinces with a high percentage of stunting. Central Aceh Regency is a district that is included in the 10th highest cases of stunting in Aceh. The incidence of stunting is very influential since the child is in the first 1000 days of life. The aim of this research is to find out the relationship between the Indonesia Healthy Family Approach Program (PIS-PK): nutritional indicators, maternal and child health with stunting in the first 1000 days of life in the Lut Tawar Community Health Center working area. Method: This research is descriptive-analytic with a cross-sectional approach. The population in this study were all mothers who had children in the first 1000 days of life in the Lut Tawar Community Health Center area, Central Aceh Regency with a total sample of 82 people. The sampling technique uses proportional random sampling. Data collection was carried out using a questionnaire, then statistical tests were carried out using the chi-square test, and data were analyzed using SPSS. Results: The results of the study showed that there was a relationship between the use of contraception/family planning (p value=0.041), delivery in a health facility (p value=0.044), complete basic immunization (p value=0.024), exclusive breastfeeding (p value=0.046) and monitoring child growth (p value=0.043) with the incidence of stunting in children in the first 1000 days of life in the Lut Tawar Community Health Center working area. Recommandation: It is hoped that the Central Aceh District Health Service will add more activities such as counseling on dietary patterns and parenting patterns in households besides PIS-PK in order to reduce the stunting rate in Central Aceh District.